2021
DOI: 10.1016/j.ebiom.2021.103450
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicenter evaluation of real time PCR Kit prototype for early diagnosis of congenital Chagas disease

Abstract: Background: Current algorithm for Congenital Chagas Disease (cCD) diagnosis is unsatisfactory due to low sensitivity of the parasitological methods. Moreover, loss to follow-up precludes final serodiagnosis after nine months of life in many cases. A duplex TaqMan qPCR kit for Trypanosoma cruzi DNA amplification was prospectively evaluated in umbilical cord (UCB) and peripheral venous blood (PVB) of infants born to CD mothers at endemic and non-endemic sites of Argentina.Methods: We enrolled and followed-up 370… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
(29 reference statements)
0
22
0
Order By: Relevance
“…To fill this gap, molecular methods in newborns or infants have been tested for sensitive early diagnosis to avoid loss to follow-up. 50 , 51 , 52 , 53 , 54 A TaqMan real-time polymerase chain reaction (qPCR) based kit, including an internal control of DNA integrity of the sample or reaction inhibition, has achieved higher sensitivity than the micromethod starting from 1 mL of peripheral blood mixed with a DNA stabiliser solution. 54 Studies in infants born to seropositive mothers have observed that the best age to carry out molecular diagnosis of congenital transmission is around the first month of life, when the parasitic load is at its peak, 49 , 55 and potential false positive results that might arise from the transmission of T. cruzi DNA from the mother to the fetus are minimised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To fill this gap, molecular methods in newborns or infants have been tested for sensitive early diagnosis to avoid loss to follow-up. 50 , 51 , 52 , 53 , 54 A TaqMan real-time polymerase chain reaction (qPCR) based kit, including an internal control of DNA integrity of the sample or reaction inhibition, has achieved higher sensitivity than the micromethod starting from 1 mL of peripheral blood mixed with a DNA stabiliser solution. 54 Studies in infants born to seropositive mothers have observed that the best age to carry out molecular diagnosis of congenital transmission is around the first month of life, when the parasitic load is at its peak, 49 , 55 and potential false positive results that might arise from the transmission of T. cruzi DNA from the mother to the fetus are minimised.…”
mentioning
confidence: 99%
“…It is yet unclear what the rate of false positive results is when using this sample source, as it might be likely contaminated with parasite DNA from maternal blood and thus lead to false positive detections. 54 , 110 , 111 …”
mentioning
confidence: 99%
“…Our data show that qPCR is a potential tool to achieve the goals of EMTCT plus detecting more than 90% of the infected infants in the first analyzed sample allowing for the implementation of early treatment. Taking into account the evidence from this and another recent study [ 30 ], the algorithm for the diagnosis of CCD should be updated to allow qPCR to be used as a tool for early diagnosis when supplies and equipment are available.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the infants included had been referred to the reference center, the youngest being 3 days old. A recent study in neonates has shown lower sensitivity in neonates studied on the first day of life [ 30 ]. These limitations could be overcome in multicenter studies that allow an evaluation of diagnostic accuracy including neonatology services, different operators in the reading of the ME, and a greater number of samples.…”
Section: Discussionmentioning
confidence: 99%
“…The rst search identi ed a total of 858 records (363 in MEDLINE/PubMed, 187 in Web of Science, 175 in EMBASE, 117 in SCOPUS, and 16 in LILACS); 611 studies were removed before screening, and 247 papers remained. In total, 71 articles were not considered relevant after title and abstract screening (52) or were not retrieved (19); 176 studies that met the inclusion criteria were reviewed in depth, and 147 studies were excluded for reasons such as lack of diagnostic accuracy data (69), samples other than blood samples (56), treatment monitoring (13), and immunocompromised patients (9). Three records identi ed by citation searching were added.…”
Section: Study Selectionmentioning
confidence: 99%